Fifty fifty - Patterson, James, 1947-; Fox, Candice (New York : Little Brown and Company, 2018)
"Detective Harriet Blue is a relentless detective--but when her own brother is accused of murder, will she self-destruct? Sam Blue stands accused of the brutal murders of three young students, their bodies dumped near the Georges River. Only one person believes he is innocent: his sister, Detective Harriet Blue. And she's determined to prove it. But Harry's outburst at her brother's trial earns her a reassignment--to the outback. With no choice but to leave Sam's case alone, she relocates to Last Chance Valley, population 75, where a diary found on the roadside outlines a shocking plan: the massacre of the entire town. And the first killing, shortly after Harry's arrival, suggests the clock is already ticking. Meanwhile, back in Sydney, a young woman holds the key to crack Sam's case wide open. If only she could escape the madman holding her hostage . . . "--Amazon.com.
Keywords: Women detectives -- Fiction; Murder -- Australia -- Fiction; Serial murderers -- Fiction; Large type books; Australia -- Fiction